Understanding Business Marketing Strategy and Its Influence on Consumer Behavior: A Qualitative Analysis - Riza M Yunus (Ilomata International Journal of Management, 2023)
The activity carried out by consumers every day is shopping. This activity is very important because it affects everyday life. In carrying out shopping activities, many decisions are made by the consumer. Understanding the consumer decision process is very important for marketers to create the right marketing strategy. This research will be carried out to look at the relationship that occurs between consumer behavior and its influence on changes in marketing strategy in Indonesia. This research will be carried out using a qualitative approach. The data used in this research comes from the results of previous research or studies that still have relevance to this research. This study found that when consumers feel a product has successfully met their needs, they will feel satisfied in consuming the product. Marketing strategy is determined by its interaction with consumer decisions. Then a good marketing strategy is to provide products that can meet the needs of consumers.